Touching the city : thoughts on urban scale - Makower, Tim (Architectural design primer., 2014)
Scale in cities is relative and absolute. It has the ability to make us feel at home in the world or alien from it; connected or disconnected. Both large and small scale in cities can be beautiful; both are right, neither is wrong. Whilst accepting that prescription is no answer, ''getting the scale right'' - at an intuitive and sensual level - is a fundamental part of the magic of architecture and urban design. Touching the City explores how scale is manifested in cities, exploring scale in buildings, in the space between them and in their details. It asks how scale makes a difference. Travel.